G302(P) The burden of youth on youth violence in a paediatric emergency department. (27th April 2016) - Leith, E; Hannon, F; Potter, S; Phillips, R; Taylor, C; Hann, G
Abstract : Aim: Like many urban boroughs, since 2007, there has been a rise in serious gang and youth violence. An innovative partnership project has been launched between the local district general hospital, borough council (A) and local youth charity tackling youth-on-youth and gang related violence. Vulnerable young people, under the age of 18, have been identified and offered dedicated support from the youth worker team. This has only been instigated for borough A and young people from the adjacent borough B have no such provision. The aim of this project was to quantify the scale of youth-on-youth violence resulting in Emergency Deparment (ED) attendance and to subsequently evaluate the number of young people who have access to youth worker services. Method: All ED attendances for young people aged 12–24 were identified from 11/9/14–5/12/14. This data was further analysed to compare attendances for borough A and B. Patients younger than 18, eligible for youth worker input, attending the ED secondary to youth-on-youth violence from 1/10/14 to 1/12/14 were identified. Results: From 11/9/14–5/12/14: × 42, 306 casualty (CAS) cards manually searched 4% (1, 522 cards) – secondary to injury 10% (156 cards) – injuries categorised as assault, in patients aged 12–24 From 1/10/14 to 1/12/14: × 52 attendances secondary to youth-on-youth violence, aged under 18 41 male: 11 female × See graph: 1 for age breakdown 2 for attendance by borough 3 for outline cost of attendances Many of this cohort attended multiple times with previous injuries, up to 11 attendances in preceding years, suggesting that gang violence was a significant part of their lives. Conclusions: The burden of youth-on-youth violence is evident. As highlighted, 52% from borough B had no available youth support. On presentation of this data, the local mayor 'Policing and Crime Office' have awarded a grant for the commissioning of a youth worker for borough B, enabling them to work 3 days a week to meet the needs of these vulnerable young people.